Oral ribavirin therapy for respiratory syncytial virus infections in moderately to severely immunocompromised patients. Issue 2 (13th March 2014) - Marcelin, J.R.; Wilson, J.W.; Razonable, R.R.; ,
Abstract Background Respiratory syncytial virus (RSV) infections may be fatal in immunocompromised patients. Aerosolized ribavirin is used for treatment, but it is very costly, teratogenic, and inconvenient. We aimed to assess the outcome of oral ribavirin treatment, with or without intravenous immunoglobulin (IVIG), for RSV infections in moderately to severely immunocompromised patients. Methods Medical records of RSV polymerase chain reaction (PCR)‐positive patients during 2011–2013 were reviewed retrospectively. Eligible patients were moderately to severely immunocompromised and received oral ribavirin (600–800 mg twice daily) with or without IVIG (500 mg/kg q 48 h) as per protocol. Results Of 96 adults with PCR‐proven RSV infection, 34 were moderately to severely immunocompromised and received oral ribavirin treatment. The mean age was 56.2 years (range: 18–90); 21 were male. Underlying conditions were hematologic malignancy with or without hematopoietic stem cell transplant (n = 25), lung transplant (n = 3), or receipt of cytotoxic chemotherapy (n = 11). The presenting symptoms were cough (94%), fever (62%), and dyspnea (59%). The most common radiographic findings were patchy and nodular infiltrates and opacities. Of 34 patients, 31 were hospitalized, with 13 admitted to the intensive care unit and 6 required mechanical ventilation. The median absolute lymphocyte count on presentation was 480 cells/mm3. RSV pneumonia developed in 24 patients. The median initial duration of oral ribavirin treatment was 10 days (range: 4–11); 4 patients were re‐treated. Of 34 patients, 19 received a mean of 2.7 doses of IVIG. Two patients had adverse reactions to ribavirin (hemolytic anemia and lactic acidosis in 1 patient, and altered mental status in another). No patient died from RSV infection. Three patients died from complications of their underlying illness; all others recovered clinically. Conclusions Oral ribavirin with or without IVIG is a well‐tolerated treatment for RSV infection in moderately to severely immunocompromised hosts. Comparative prospective studies should ideally be performed to determine if oral ribavirin is the optimal therapy for RSV infection in this patient population.